Preservice primary school teachers’ intention to teach national identity education: evidence from Kazakhstan - Nurbek Sabanbayev; Gulsum Ayapbergenova; Almash Turalbayeva; Arman Nurmakhanbetov; Serik Kastayev; Saniya Nurgaliyeva (Institute of Advanced Engineering and Science, 2026)
Fostering national identity (NI) in primary school students is essential for promoting civic awareness and supporting sustainable national development. Early school years are particularly critical for shaping NI, which places additional demands on teachers and the primary education system. Pre-service primary school teachers (PPSTs) often face challenges in translating their intentions to teach national identity (INTNI) into classroom practice. This study investigated the factors influencing these teachers’ intentions and the mechanisms through which these intentions develop. Drawing on the theory of planned behavior (TPB) and social identity theory (SIT), data were collected from 254 pre-service teachers at a Kazakhstani university and analyzed using partial least squares structural equation modeling (PLS-SEM). Results revealed that institutional resources shape teachers’ intentions indirectly by enhancing attitudes toward teaching NI, teaching self-efficacy, and national identity awareness (NIA), while direct effects were not significant. Internalization of national values (INV) had a weaker but meaningful impact. The findings highlight the importance of teacher education programs emphasizing professional confidence, positive attitudes, and identity awareness to prepare teachers effectively for implementing NI education in primary schools.